1987
DOI: 10.1073/pnas.84.24.8854
|View full text |Cite
|
Sign up to set email alerts
|

Mode of substrate carboxyl binding to the [4Fe-4S]+ cluster of reduced aconitase as studied by 17O and 13C electron-nuclear double resonance spectroscopy.

Abstract: The active form of aconitase has a diamagnetic [4Fe-4S]21 cluster. A specific iron ion (Fea, which is lost during inactivation) is the binding site for substrate, as shown by Mossbauer spectroscopy. We have studied the mode of substrate and analogue binding at equilibrium to the paramagnetic [4Fe-4S]+ cluster of the reduced active form by 170 and 13C electron-nuclear double resonance spectroscopy with specifically labeled substrates. The data show that with substrate, only the carboxyl at C-2 of the propane ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
37
0
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 15 publications
8
37
0
1
Order By: Relevance
“…Inasmuch as we have been unable to prepare an enzyme that contains more than one-half of a [4Fe-4S] cluster per subunit (31), it is possible that only two of the cysteine residues are ligated to the cluster, which is shared between two subunits. Another explanation would suggest a cluster ligated to the protein with only three cysteine residues, the fourth ligation site being occupied by a water or hydroxide ion, as in the case of aconitase (23,43), or by another amino acid side chain.…”
Section: Discussionmentioning
confidence: 99%
“…Inasmuch as we have been unable to prepare an enzyme that contains more than one-half of a [4Fe-4S] cluster per subunit (31), it is possible that only two of the cysteine residues are ligated to the cluster, which is shared between two subunits. Another explanation would suggest a cluster ligated to the protein with only three cysteine residues, the fourth ligation site being occupied by a water or hydroxide ion, as in the case of aconitase (23,43), or by another amino acid side chain.…”
Section: Discussionmentioning
confidence: 99%
“…Aconitase activity (i.e., the conversion of citrate to isocitrate) is mediated by an essential redox inactive iron-sulfur center. The [4Fe-4S] center is necessary for the binding of the C-2 carboxyl of citrate or cis-aconitate and for the binding of the C-1 carboxyl of isocitrate (18). This coordination of binding occurs through the labile fourth iron atom designated Fe a .…”
Section: Vol 184 2002mentioning
confidence: 99%
“…Mossbauer (Kent et al, 1982;Emptage et al, 1983b) and electron-nuclear double resonance (ENDOR; Telser et al, 1986;Kennedy et al, 1987;Werst et al, 1990a) spectroscopic studies have revealed that Fe;, has, in addition to three inorganic sulphur bridging ligands, a hydroxyl anion ligand which persists but becomes protonated upon binding of the C2 carboxylate anion of cis-aconitate to Fe,. The inequivalence of the iron sites in the cluster has been highlighted by 57Fe-ENDOR and "S-ENDOR and it has been further shown that the nuclei of two of the inorganic sulphide bridging ligands are considerably more strongly coupled to the paramagnetic electron density in the reduced [4Fe-4S] ' cluster than are those of the other two (Werst et al, 1990b).…”
mentioning
confidence: 99%